Analysis of banned veterinary drugs and herbicide residues in shellfish by liquid chromatography-tandem mass spectrometry (LC/MS/MS) and gas chromatography-tandem mass spectrometry (GC/MS/MS). Issue 1 (15th December 2016) - Chang, Geng-Ruei; Chen, Hui-Shan; Lin, Feng-Yi
Abstract: Seafood safety is a crucial public health concern for consumers. In this study, we applied a validated method to analyze the residue of banned veterinary drugs in shellfish, namely chloramphenicol, malachite green, leucomalachite green, and nitrofuran metabolites; additionally, the QuEChERS method was employed to detect 76 herbicides by LC/MS/MS and GC/MS/MS. In total, 42 shellfish samples, which included hard clams, freshwater clams, and oysters, were collected from aquafarms and production areas in Taiwan during 2012. Our results revealed 3.8 ng/g of chloramphenicol in one hard clam, 19.9–32.1 ng/g of ametryn in two hard clams, 16.1–60.1 ng/g of pendimethalin in four hard clams, and 17.0 ng/g of mefenacet in one oyster, indicating that 19.1% of the samples contained residues from banned veterinary drugs and pesticides. These data can be used to monitor the residue of veterinary drugs and pesticides in aquatic organisms and as a reference for food safety. Highlights: A certified method was employed for analyzing residues of banned veterinary drugs and herbicides in shellfish samples. The trace levels of chloramphenicol, ametryn, pendimethalin were detected in hard clam samples. For ensuring food safety, continual monitoring of aquatic products is necessary.